2020
DOI: 10.1186/s40900-020-00230-5
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with patients to get better outcomes with chimeric antigen receptor T-cell therapy: towards engagement of patients in early phase trials

Abstract: Aim Though patient engagement in clinical research is growing, recent reports suggest few clinical trials report on such activities. To address this gap, we describe our approach to patient engagement in the development of a clinical trial protocol to assess a new immunotherapy for blood cancer (chimeric antigen receptor T-cell therapy, CAR-T cell therapy). Methods Our team developed a clinical trial protocol by working with patient partners from inception. Two patient partners with lived blood cancer experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…For example, patient partners have provided feedback on the trial protocol, consent forms, visual aides, and lay summaries, and in developing plans to organise a patient peer support panel. 58 …”
Section: Discussionmentioning
confidence: 99%
“…For example, patient partners have provided feedback on the trial protocol, consent forms, visual aides, and lay summaries, and in developing plans to organise a patient peer support panel. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Establishing partnerships with patients and patient groups (PGs) to engage them in all levels of clinical trials (CTs), including in real-world evidence research, is increasingly explored and applied globally [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Keys to such engagement—also referred to as co-design research, participatory research, patient-oriented research (POR), patient-involved research, patient public involvement, patient participation, co-creative research, citizen science, patient-centric initiative, open science—are the understanding and the manifestation of the concept of patient centricity or patient centeredness [ 1 , 3 , 4 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of involving the end-user groups in the broad research agenda include increased research relevance to both clinicians and patients [ 1 ], with positive impacts reported in setting research priorities, developing proposals, recruiting and retaining patients, as well as disseminating results, including societal and ethical benefits [ 2 , 4 , 7 , 9 , 10 , 14 , 28 , 29 , 30 , 31 , 32 , 33 ]. Guidelines and recommendations are emerging on research partnerships with patients, which support the principles of trust, respect, and co-learning [ 2 , 7 , 13 , 18 , 19 , 22 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations